Nymphaea nouchali Burm. f. hydroalcoholic seed extract increases glucose consumption in 3T3-L1 adipocytes through activation of peroxisome proliferator-activated receptor gamma and insulin sensitization - Mabel Parimala; M Debjani; Hannah Rachel Vasanthi; Francis Gricilda Shoba (Wolters Kluwer Medknow Publications, 2015)
Nymphaea nouchali Burm. f. (Family - Nymphaeaceae) is a well-known medicinal plant used in the Indian ayurvedic system of medicine for treating diabetes. The seeds especially have been prescribed for diabetes. The hydroalcoholic extract of N. nouchali seeds has been demonstrated to possess anti-hyperglycemic effects in diabetic rats, but the functional mechanism remains unknown. The nuclear receptor, peroxisome proliferator-activated receptor gamma (PPARγ) is noted to play an important role in glucose and lipid homeostasis. This study was hence focused in evaluating the effect of the extract on PPARγ activation, adipocyte differentiation, and glucose consumption in 3T3-L1 cells. Cell viability was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT), followed by adipogenesis assay using Oil Red O technique. Glucose consumption of preadipocytes and adipocytes in the presence of the extract was also determined. Real-time polymerase chain reaction was performed to identify the expression of genes involved in glucose consumption in the adipocytes. MTT assay confirmed the extract to be nontoxic, and Oil Red O staining confirmed enhanced adipocyte differentiation of 3T3-L1 cells in a dose-dependent manner. The extract also increased the expression of PPARγ target gene, which in turn enhanced the expression of GLUT-4. The data, therefore, suggests that N. nouchali seed extract promotes adipocyte differentiation and glucose consumption by inducing PPARγ activation, which in turn increases mRNA GLUT-4 expression and subsequently enhances insulin-responsiveness in insulin target tissues.